نون الوقاية مواضعها وأحكامها - بنت عبد العزيز الخضير, مها (جامعة الوادي - university of Eloued, 2022)
تناول البحث موضوع ( نون الوقاية )، التي تلحق أواخر بعض الكلمات عند إسنادها لياء المتكلم، وبيان درجات حكم إثباتها أو حذفها، مع ذكر التعاليل المؤيدة لذاك الحكم على غيره، كما بين البحث مواضع لحاق هذه النون وأثرها على مدخولها، مع كونه يدور حول حرف واحد إلا أنه غاية في الأهمية لما يقوم به هذا الحرف من دور في الحفاظ على قواعد اللسان العربي وحفظ حدوده. This research is talking about (Prevention N) which comes at the end of some words when they are added to the objective pronoun (Me). Also, it indicates when it should be added or removed with mentioning the reasons behind each judgment. In addition, it talks about the different adding position of (N) to the word and its effect on it Although it is one letter, but it plays a very significant role in protecting the grammar of Arabic language.
مقال
Keywords: الوقاية؛المواضع؛ الأحكام؛ الأثر; protection-Placements-Provision-Impact